دور الرضا الوظيفي في أداء العاملين - حمزة, صياد (جامعة المسيلة, 2021)
In this research, entitled The Impact of Job Satisfaction in Improving the Performance of the Human Resource in Directorate of Transport for The State of Mesila, we discussed the validity of the questions represented in: 1. What is the relationship between job satisfaction and employee performance? 2. What is the level of job satisfaction of individuals working in the institution? 3. What is the level of performance of individuals working in the institution? Through these questions, we tried to find out the impact of job satisfaction in improving the performance of the human resource in the Directorate of Transport for The State of Mesila. It has a significant impact on improving the performance of the human resource in the National Employment Agency, and also gives them the ability to master work and acquire new knowledge, and this is what makes him navigate this world without feeling time, and this leads to job satisfaction.
دراسة حالة:مديرية النقل ولاية المسيلة